2021
DOI: 10.3390/ijms22126325
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of FA5, a Novel AMP-Activated Protein Kinase (AMPK) Activator as an Innovative Drug for the Management of Bowel Inflammation

Abstract: Acadesine (ACA), a pharmacological activator of AMP-activated protein kinase (AMPK), showed a promising beneficial effect in a mouse model of colitis, indicating this drug as an alternative tool to manage IBDs. However, ACA displays some pharmacodynamic limitations precluding its therapeutical applications. Our study was aimed at evaluating the in vitro and in vivo effects of FA-5 (a novel direct AMPK activator synthesized in our laboratories) in an experimental model of colitis in rats. A set of experiments e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The role of AMPK in intestinal health has received increasing attention in recent years [ 10 , 27 ]. Studies using mouse models of colitis have showed a correlation between the decrease in intestinal AMPKα Thr172 phosphorylation (the active form of AMPK) and colitis development [ 15 , 17 , 28 ]. Interestingly, reduction in AMPKα Thr172 phosphorylation was also observed in the intestine of IBD patients and appeared to occur in both epithelial and lamina propria compartments [ 17 ], further highlighting the underlying connection between AMPK and intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AMPK in intestinal health has received increasing attention in recent years [ 10 , 27 ]. Studies using mouse models of colitis have showed a correlation between the decrease in intestinal AMPKα Thr172 phosphorylation (the active form of AMPK) and colitis development [ 15 , 17 , 28 ]. Interestingly, reduction in AMPKα Thr172 phosphorylation was also observed in the intestine of IBD patients and appeared to occur in both epithelial and lamina propria compartments [ 17 ], further highlighting the underlying connection between AMPK and intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…The colon was collected from mice and flushed of fecal content with ice-cold phosphate-buffered saline (PBS), as described previously (Antonioli et al, 2021). Tissues were minced and homogenized using a Potter-Elvehjem Grinder homogenizer on ice in 20% (w/v) TNE lysis buffer (50 mM Tris-HCl pH 7.4, 100 mM NaCl, 0.1 mM EDTA, 1% NP-40, 1% SDS, 0.1% DOC) with proteases and phosphatases inhibitors.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Myeloperoxidase was assumed as a quantitative index to estimate the degree of mucosal infiltration by polymorphonuclear cells and, thereby, the severity of enteropathy elicited by diclofenac. MDA concentration in intestinal tissues was determined to obtain quantitative estimates of membrane lipid peroxidation (Antonioli et al, 2021;Fornai et al, 2020). MPO and MDA levels in the ileum were assessed according to previously adopted methods (Antonioli et al, 2021;Fornai et al, 2020), described in the supporting information.…”
Section: Evaluation Of Tissue Myeloperoxidase (Mpo) and Malondialdehy...mentioning
confidence: 99%
“…MDA concentration in intestinal tissues was determined to obtain quantitative estimates of membrane lipid peroxidation (Antonioli et al, 2021;Fornai et al, 2020). MPO and MDA levels in the ileum were assessed according to previously adopted methods (Antonioli et al, 2021;Fornai et al, 2020), described in the supporting information.…”
Section: Evaluation Of Tissue Myeloperoxidase (Mpo) and Malondialdehy...mentioning
confidence: 99%